2014
DOI: 10.1017/s136510051300093x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Misallocation and Growth

Abstract: We develop a growth model where knowledge is embodied in individuals and diffused across sectors through labor mobility. The existence of labor mobility costs constrains mobility and thus generates labor misallocation. Different levels of labor misallocation imply different levels of exploitation of available knowledge and therefore different total factor productivity across countries. We derive a positive relationship between growth and labor mobility, which is consistent with the empirical evidence, by assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, it could also be due to the fact that knowledge might be more industry oriented (although it can be used in other sectors). Thus, the profitability of one firm's R&D for all other firms would depend on the sector in which the other firms operate (as in Raurich et al ., ).…”
Section: Randd‐variety Growth Models and Scale Effectsmentioning
confidence: 97%
“…However, it could also be due to the fact that knowledge might be more industry oriented (although it can be used in other sectors). Thus, the profitability of one firm's R&D for all other firms would depend on the sector in which the other firms operate (as in Raurich et al ., ).…”
Section: Randd‐variety Growth Models and Scale Effectsmentioning
confidence: 97%
“…It is through creative destruction that new generations of technology replace the previous ones; in the current paper, this creative destruction exists, leaving behind those who cannot adapt to the use of new techniques. Technological obsolescence may be, as well, associated with the extent in which knowledge is misallocated [Raurich et al (2015)].…”
Section: Technological Obsolescencementioning
confidence: 99%
“…As also found that increased labour mobility between foreign and local firms results in increased job creation by local firms [6]. Also, [7] while assuming constant returns to capital proved that labour mobility and growth works in the same direction. As labour mobility increases, growth increases.…”
Section: Introductionmentioning
confidence: 99%